Management Of Educational Facilites and Infrastructure at SDN 10 KUNPAR - Tugiah Tugiah (IAIN Batusangkar, 2022)
: Based on the phenomena that are around us, especially at SDN 10 Kunpar which incidentally is located in an area that is indeed far from the center of the crowd and public facilities that make it possible for the school to be better than other schools so that it can be an inspiration or pilot and become a dream school for the local community. Meanwhile, the SungaiTenang community has always longed for schools in the area to be able to make schools that are indeed their targets for educating students, to be calmer, more enthusiastic and do not need to look for other schools. Meanwhile, if seen from the reality so far, the school has not met the requirements desired by the community. With the fact that there is so that the principal thinks how to improve the facilities and Infrastructure that doesn't exist yet and is, of course, a common homework, it will not be able to be done by the principal or the teacher who is there alone, including how to manage the facilities and infrastructure after all that materialized